Mechanics Parameter Optimization and Evaluation of Curtain Grouting Material in Deep, Water-Rich Karst Tunnels - Hai Shi; Mingzhou Bai; Shaochuan Xing (Advances in Materials Science and Engineering)
Mud and water often gush suddenly during the construction process of deep buried karst tunnels, which may cause serious accidents and result in major economic losses. Accordingly, for tunnels buried in deep rich water districts, discovering how to effectively control water gushing and ensure the stability of surrounding rock has great influence on the safety of engineering construction. The case study in this paper simulates the water-rich section of Dou-mo tunnel from Shanghai to Kunming of China. Numerical analysis was used to simulate the construction of the curtain grouting section and to evaluate the effects of the various curtain grouting parameters. The optimal grouting parameters were selected and then evaluated by applying them to the grouting method. The results show that (1) the grouting effect is the most notable one when the thickness of the grouting circle is outside the 4 m range of the tunnel contour. (2) In the same circle, the grouting quantity of the same ring is presented as a wave form. Therefore the number of the same ring grouting holes should reduce and increase the distance between the adjacent grouting holes appropriately to reduce the number of grouting holes and speed up the grouting progress.